Molecular Characterisation Of Clostridium Perfringens Isolates From Patients At Groote Schuur Hospital - Monki, Thembisa (Department of Pathology, 2024)
Clostridium perfringens is a spore-forming bacterium isolated from various mammals and birds. In humans it causes infections ranging from non-lethal diarrhoea to tissue-destructive, lethal diseases. Infection originates from spores found in environmental reservoirs such as soil, faecal-contaminated water, and food. Infection can also be caused, when the organisms disseminate from the gastrointestinal tract (GIT) of human carriers to the rest of the body. South Africa (RSA) lacks published data on the specific strains and toxin types responsible for human clostridial infections, as only identification and drug susceptibility testing are done in routine laboratories. The main aim of this study was to characterise 19 clinical isolates of C. perfringens (collected between 2017- 2020) using phenotypical and molecular methods such as PCR-based toxin typing, antimicrobial susceptibility testing and whole genome sequencing. Strains were isolated from patients with invasive clostridial disease. In agreement with other studies, toxin typing confirmed that all isolates encode the Phospholipase C (plc) gene which encodes for the tissue-destructive alpha toxin. Of the 19 isolates tested, 16⁄ 19 (84 %) belonged to Type A, i.e., these isolates only contained the alpha toxin (cpa) and not the other toxins used for profiling. The remaining 16% belonged to type F, thus code for both alpha and enterotoxin (cpe). Toxin types B, C, D, E and G, i.e., strains with PCR amplicons for the beta, epsilon, iota and NetB genes, were not found amongst this set of isolates. All isolates were susceptible to the antibiotic piperacillin (and its lactamase inhibitor partnertazobactam), the carbapenem imipenem and the fluoroquinolone moxifloxacin. Clinical resistance was observed against amoxicillin/clavulanic acid (5%) and penicillin G (10%). Overall, the least effective antibiotics were clindamycin (68%) and metronidazole (68%), with isolates exhibiting either intermediate or complete resistance. Whole genome analysis of a subset of 5 mono-and multidrug resistant (MDR) isolates did not reveal known resistance factors encoding for metronidazole resistance, but the genetic determinant for macrolide resistance (ermQ) was identified in one clindamycin resistant isolate. WGS also revealed that the genome of 1/5 isolates clustered with previously published human isolates originating from non-lethal gastroenteritis cases, although the enterotoxin (cpe) gene was not identified either via PCR-based toxin typing or whole genome analysis. The genomes of the remaining 4/5 isolates cluster with published genomes originating from the environment, birds, or unidentified animals. Multi-locus sequencing type (MSLT) reveals two isolates (GSH 46 and GSH 48) belonged to a single MLST ST274, 2 indicating that they were from the same origin.